El principio constitucional de laicidad en Francia: a un año del atentado contra Charlie Hebdo - Revilla Izquierdo, Milagros Aurora (2016)
The attack on Charlie Hebdo in January 2015 caused political statements and academic reflections principally on the danger to constitutional principle of french laicism and republican values, without detriment to the references to freedom of expression and other rights as to the relationship with terrorist attacks in november 13 in Paris in the same year. The purpose of this work is the understanding and application of this constitutional principle in the present circumstances in France. The point of reference is the legal basis, the recent national jurisprudence and consideration of this in the international legal community.